Perubahan Konsentrasi Oksigen Terlarut dan pH Perairan Tambak setelah Penambahan Rumput Laut Sargassum Plagyophyllum dan Ekstraknya - Izzati, Munifatul (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2008)
Shrimp-seaweeds polyculture is a model of sustainable ecosystem. The aim of this system is to increasewater quality and shrimp production. This research is to test the efectivity of shrimp-life Sargassum andshrimp-Sargssum extract. The reason in using of Sargassum extract is to increase shrimp production, asthis seaweeds produce phlorotanin that is effectively kill several pathogenic bacteria. Hereby, the additionof Sargassum extract will also affect oxygen concentration and pH. Therefore, it is important to analyze itseffect on dissolve oxygen and pH. Results indicated that, the presence of life Sargassum increased oxygenconcentration and pH at the beginning. However, destruction of life Sargassum by rain was ended inreduction of both, dissolved oxygen and pH. Addition of Sargassum extract reduced dissolved oxygen andpH. It was predicted that Sargassum extract would increase the content of organic material that stimulateoxygen consumption during degradation process. However, the presence of phlorotanin also inhibitdegradation process, therefore it is degraded slowly.